'Montevideo del 900': - Tomeo, Daniela (Universidad Centro Latinoamericano de Economía Humana (Universidad CLAEH), 2020)
This article reflects on the presence of female plastic artists in Uruguay between the second half of the 19th century and the first decade of the 20th century, revealing the logics as well as the places from which the society of the time enabled the participation of women in the field of arts.